2004
DOI: 10.1007/bf03192524
|View full text |Cite
|
Sign up to set email alerts
|

Home ranges and movement patterns in a vulnerable polecatMustela putorius population

Abstract: 2004. Home ranges and movement patterns in a vulnerable polecat Mustela putorius population. Acta Theriologica 49: 247-258.Home range characteristics and movement patterns of four female and six male polecats Mustela putorius Linnaeus, 1758 were studied in Luxembourg using radio--telemetry. Home range size of polecats ranged from 42 to 428 ha with an average of 181 ha. The mean (± SE) home range size of males of (246 ± 45 ha) was significantly larger than that of females (84 ± 17 ha). Polecats concentrated 50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
0
7
0
1
Order By: Relevance
“…Indeed, male ferrets increase their displacement, whereas female movements were very restricted (Moors and Lavers 1981). These behaviours have also been observed in the polecat (Brzezinski et al 1992;Lode´2001), the mink (Gerell 1970;Yamaguchi et al 2004) and the otter (Rosoux 1998), whereas the increase of male home range size has been described in the stoat (Erlinge and Sandell 1986), the weasel (Erlinge 1995), the pine marten (Zalewski and Jedrzejewski 2006) and the polecat (Baghli and Verhagen 2004) during the breeding season.…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, male ferrets increase their displacement, whereas female movements were very restricted (Moors and Lavers 1981). These behaviours have also been observed in the polecat (Brzezinski et al 1992;Lode´2001), the mink (Gerell 1970;Yamaguchi et al 2004) and the otter (Rosoux 1998), whereas the increase of male home range size has been described in the stoat (Erlinge and Sandell 1986), the weasel (Erlinge 1995), the pine marten (Zalewski and Jedrzejewski 2006) and the polecat (Baghli and Verhagen 2004) during the breeding season.…”
Section: Discussionmentioning
confidence: 85%
“…Besides its apparent effect on space use in various predators (Sakaguchi 1994;Schmidt et al 1997;Kovach and Powell 2003;Baghli and Verhagen 2004;Herfindal et al 2005), reproductive strategies have been found to influence activity patterns in the Eurasian lynx (Schmidt 1999) and pine marten (Zalewski 2000(Zalewski , 2001. Such effects were also shown for movement patterns of the lynx (Jędrzejewski et al 2002) and Iriomote cats (Schmidt et al 2003).…”
Section: Discussionmentioning
confidence: 98%
“…The sampling method did not affect the SSR, as the results of all methods (trapping/hunting, live trapping or road-kills) were malebiased. The males spend on average 1.3-3.6 times more time patrolling their home-ranges than females (Lodé, 1999;Baghli and Verhagen, 2004), which may increase their encounter rates with both traps and roads. This is because males have home-ranges 2.0-5.3 times larger (Lodé, 1994(Lodé, , 1999Baghli and Verhagen, 2004;Rondinini et al, 2006), a potential bias that it is difficult to control for, as it is common to the three sampling methods.…”
Section: Discussionmentioning
confidence: 99%